Nilai Budaya Jawa dalam Antologi Puisi Tegalan Gendu Gendu Rasa Karya Dosen dan Guru Pantura Serta Implikasinya terhadap Pembelajaran Bahasa Indonesia di SMA - Julieta Niela Salma; Leli Triana; Syamsul Anwar (Journal on Education, 2023)
The purpose of this study describes the value of Javanese culture in the Tegalan GenduGendu Rasa Poetry Anthology by Pantura Lecturers and Teachers and describes the implications of research results on Indonesian learning in high school. This research is the source of the data in the form of an Anthology of Tegalan Gendu-Gendu Rasa Poems by Pantura Lecturers and Teachers. The form of data for this study is the passage of verses in the lines of poetry. This research uses a qualitative descriptive approach. The technique of providing data in this study is to use reading techniques, and note-taking techniques as an advanced technique. Data analysis in this study used the presentation of the results of data analysis using informal methods. . The results of this study show that there are 37 Javanese cultural values which include (1). the value of beliefs, (2). achievement value, (3). the value of patience, and (4). alignment value. The results of this study can be implied in Indonesian language learning in high school class X even semester in basic competencies (KD) 3.17. and basic competencies or (KD) 4.17.